A coupled-channel deperturbation treatment of the X2Σ+∼A2Π∼B2Σ+ complex of the CN radical towards spectroscopic accuracy. (December 2022) - Terashkevich, V.A.; Pazyuk, E.A.; Stolyarov, A.V.; Yurchenko, S.N.
Highlights: A global deperturbation analysis of the experimental term values of the X 2 Σ +, A 2 Π and B 2 Σ + states of the 12 C 14 N was performed using the reduced 4$×$4 coupled-channel deperturbation model. The explicit treatment of the J − depend ing σ − and Λ − -doubling effects caused by the remote states has significantly improved accuracy of the description of the X ∼ A ∼ B complex. The optimized interatomic potentials and electronic coupling functions describe the rovibronic term values of the complex on a spectroscopic level of coincidence. The mass-invariant deperturbation parameters can extend a line-list into a wide region of vibrational and rotational quantum numbers for all CN isotopomers. Abstract: A global deperturbation analysis of the experimental rovibronic term values of the X 2 Σ +, A 2 Π and B 2 Σ + states of the 12 C 14 N isotopomer has been performed. The inverse spectroscopic problem was directly solved in the framework of the reduced 4 × 4 coupled-channel (RCC) deperturbation model based on potential energy curves (PECs) as well as the spin-orbit and L -uncoupling electronic matrix elements between the X 2 Σ +, A 2 Π, and B 2 Σ + states. Regular perturbations of the X ∼ A ∼ B complex by the remote doublet states manifold were taken into account by introducing of the fine-structure parameters as explicit functions of interatomic distance. The optimized PECs and non-adiabatic coupling functions describe the vast majority (5600–6570) of the empirical term values, attributed to locally and regularly perturbed levels of the complex, with a root-mean-squared deviation of 0.015-0.05 cm − 1, depending on a particular set of the experimental term values included in the fitting procedure. The resulting mass-invariant RCC deperturbation parameters can straightforwardly extend a line-list of all CN isotopomers into a wide region of vibrational and rotational quantum numbers.